[en] SOME CONSIDERATIONS ON THE USE OF FREQUENCIES ABOVE 10 GHZ IN TROPICAL REGIONS - CLAUDIO MONTEIRO EINLOFT (MAXWELL, 2008)
[pt] Este trabalho examina o problema da atenuação por chuvas na propagação da energia em freqüências superiores a 10 ghz, com especial ênfase na aplicação dos resultados em regiões de clima tropical. São discutidos em detalhes os métodos existentes para caracterizar a distribuição estatística pontual da precipitação em uma região. Apresenta-se uma solução semi-empírica para a questão da não uniformidade espacial da distribuição de chuvas em um percurso, empregando o conceito de precipitação equivalente e dados de inúmeros trabalhos experimentais publicados na literatura técnica para diversas freqüências e distancias. Finalizando é feito um exemplo ilustrativo do método proposto, tomando por base os dados pluviográficos do Rio de Janeiro. === [en] This work deals with the problem of rainfall attenuation at frequencies above 10 GHz. Particular enphasis is given to the application of the final results for communications links in a tropical region. The proposed nethods to characterize the punctual rainfall statistical distribution in a specific region are discussed in detail. A solution to the problem of a non-uniform spatial distribution of the rainfall through the propagation path is presented, the concept of equivalent precipitation being applied. A big amount of experimental data from the technical literature was utilized, for different frequencies and distances. Finaly, an example of the proposed method is presented, along with an application based upon Rio de Janeiro rain data.